Balancing Conflicting Supply Chain Stakeholder Interests: The Big Procurement Practioner’s Dilemma - Ndolo, Jackson; Njagi, Eunice (Archives of Business Research, 2016)
Effective supply chain management practices dictate fair and balanced treatment of all critical players in any organization’s supply chain for better performance. Each of the players has their interests though occasionally some are shared; this scenario puts the position of the procurement professionals at crossroads with buyers and suppliers as they implement their employers’ objectives within a regulated environment. The paper explores the dilemma created by variant stakeholder interests in the procurement system and proposes a consultative and tradeoff approach for procurement professionals so as to achieve desired goals. The researchers surveyed all 74 procurement professional who attended the first KISM procurement research forum held at New Stanley Hotel in Nairobi in June 2014; opinions were sorted using semi structured questionnaires and analyzed using SPSS. The study focused mostly on public sector procurement practitioners since the stakeholders are similar as stipulated by the existing legal framework; private regulations mostly vary from organization to another depending on governance and positioning of procurement. Majority of the procurement professionals cited balancing of variant stakeholder interests as their biggest challenge.